2021
DOI: 10.2147/ott.s274623
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of LncRNA DARS-AS1 Inhibits the Tumorigenesis of Cervical Cancer via Inhibition of IGF2BP3

Abstract: Background Evidence has been shown that long noncoding RNAs (lncRNAs) play an important role in the development of cervical cancer. Recently, lncRNA DARS-AS1 was reported to be dysregulated in several cancer types; however, the role of DARS-AS1 in cervical cancer remains unclear. Methods Flow cytometry and transwell invasion assays were performed to determine the apoptosis and invasion in cervical cancer cells. In addition, RNA pull-down and fluorescence in situ hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Although the function role of DARS-AS1 has been extensively investigated in various malignant tumors, such as renal cell carcinoma [ 14 ], hepatocellular carcinoma [ 34 ], and thyroid cancer [ 35 ], insufficient evidence has been shown to conclude its potential mechanism acting on OC. According to the results of the GEPIA 2 database and qRT-PCR, we found that compared to normal ovarian tissues and human normal ovarian epithelial cell line, the OC tissues and OC cell lines showed elevated lncRNA DARS-AS1 expression, which was supported by other studies [ 36 , 37 ]. A2780 is a human epithelial OC cell line isolated from untreated females with OC, with strong migration and invasion ability due to its weak adhesion to the matrix membrane.…”
Section: Discussionsupporting
confidence: 83%
“…Although the function role of DARS-AS1 has been extensively investigated in various malignant tumors, such as renal cell carcinoma [ 14 ], hepatocellular carcinoma [ 34 ], and thyroid cancer [ 35 ], insufficient evidence has been shown to conclude its potential mechanism acting on OC. According to the results of the GEPIA 2 database and qRT-PCR, we found that compared to normal ovarian tissues and human normal ovarian epithelial cell line, the OC tissues and OC cell lines showed elevated lncRNA DARS-AS1 expression, which was supported by other studies [ 36 , 37 ]. A2780 is a human epithelial OC cell line isolated from untreated females with OC, with strong migration and invasion ability due to its weak adhesion to the matrix membrane.…”
Section: Discussionsupporting
confidence: 83%
“…This gene encodes a member of a multi-enzyme complex that its role has been proved in mediating attachment of amino acids to their cognate tRNAs. Some studies have reported that DARS-AS1 gene (encoding a long noncoding RNA) act as an oncogene ( 98 ) and is positively associated with the pathological stages in thyroid and ovarian cancer by targeting mir-129 and mir-532-3p, respectively ( 99 , 100 ). Moreover, this gene is directly upregulated by HIF1 gene, which stabilizes RBM39 protein in Myeloma ( 101 ).…”
Section: Discussionmentioning
confidence: 99%
“…ensembl.org/Homo_sapiens/Gene/Summary?g = ENSG00000231890; r = 2:135985124-136022593). As an antisense lncRNA, DARS-AS1 has emerged as a recognized oncogenic entity, implicated in a wide array of cancer types as supported by extensive research publications [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51], as depicted in Figure 1. These encompass cancers originating from various organ systems, including the digestive, urinary, respiratory, female reproductive, hematological, and neurological systems, among others.…”
Section: Ivyspringmentioning
confidence: 99%